تجلّيات مفهوم التّنوع الثّقافي في الدّرس المقارن الجزائري - الأدب المقارن وقضايا الحوار الثّقافي، التّعدّيّة الثّقافية وهجنة الهويّات-: Manifestations of the concept of cultural diversity in the Algerian comparative lesson J Comparative literature and the issues of cultural dialogue cultural pluralism and hybrid identities - بوسكين هجيرة (Maalim, 2021)
With the remarkable increase in the level of interculturalism in the era of globalization, it has become difficult to study any culture or literature outside the framework of comparison, due to the important role of comparison in revealing the characteristics of each culture and the degree of its interference and dialogue with other cultures. Accordingly, this article t tries to investigate the manifestations of the concept of cultural diversity and the various issues related to it in the field of Algerian comparative studies, considering that comparative literature is a suitable field for studying the various aspects of cultural and civilizational contact between peoples. Keywords: cultural diversity; Algerian comparative lesson; Cultural dialogue; Cultural pluralism; the hybridization of identities.